Students as First-time Voters: The role of Voter Advice Applications in Self-reflection on Party Choice and Political Identity - Kristensen, Niels Nørgaard; Solhaug, Trond (JSSE - Journal of Social Science Education, 2017)
Purpose: This article analyses what characterises first time voters' self-reflections on party choice as they use voter advice applications. Method: This study is based on interviews of 28 Norwegian students (age 18-20)preparing themselves for their first election. Findings: Finding a party to vote for is primarily characterized by a process of matching a party to students' political self, which we see as steps toward a political identity. Practical implications: Teaching politics should allow for students' reflections on self and their political preferences.